A map of terror for the last phase of the years of lead: State Security Force victims in the Basque Country (1982-1994) - Mota-Zurdo, David (Revista de Estudios Andaluces, 2021)
This article is a quantitative analysis of the victims, members of the State Security Forces, who were murdered by ETA and other terrorist groups in the Basque Country between 1982 and 1994. Starting from a territorial perspective, is emphasized on the origin of the victims, in their place of murder and in the police force which they belonged: the purpose is to get a panoramic photo of the impact that the terrorist actions had against the State Security Forces in Euskadi. Without making a detailed analysis of each victim, this research analyzes and compares the data of those who were civil guards, police and military using a descriptive methodology and a positivist approach. The objective of the article, what is to verify which police and military force was the most affected by terrorist violence and to highlight those Basque towns, regions and provinces that were the deadliest, is met after concluding that Gipuzkoa was the main place of death of the members of the Security Forces, being the Castilian-Leonese, and not the Andalusians, the most affected by terrorism.